Association of Length of Stay and COVID-19 in Rotational Ankle Fracture Surgery in the National COVID Cohort Collaborative (N3C). Issue 1 (January 2022) - Pitts, Charles C.; Levitt, Eli; Patch, David A.; Terrero, Alfredo; Butler, Reed; Ponce, Brent A.; Theiss, Steven M.; Spitler, Clay A.; Johnson, Michael D.
Category: Ankle; Trauma Introduction/Purpose: Coronavirus (COVID-19) is an emerging, rapidly evolving situation. The National COVID Cohort Collaborative (N3C) is an innovative approach to integrate real-world clinical observations into a harmonized database. To investigate the outcomes of adults with ankle fracture surgery during the (COVID-19) pandemic, we had the following research question: What are the outcomes of ankle fracture patients with COVID-19 (invasive ventilation, length of stay, death)? The purpose of this abstract is to introduce the largest cohort of ankle fracture patients to date with a comparison between lab- confirmed COVID-19-positive and COVID-19-negative. Methods: A retrospective cohort of adults with ankle fracture surgery in the N3C Data Enclave. The N3C Data Enclave is an NIH-funded, secure platform through which the harmonized clinical data from electronic health records is stored (https://covid.cd2h.org/ ). COVID-19 status was determined using a set of 55 SARS-CoV-2 polymerase chain reaction and antigen lab tests. Ankle fracture surgery was defined using SNOMED codes for 'fracture of bone' and one of the following CPT codes '27766, 27769, 27792, 27814, 27822, 27823, 27829' for 'ankle fracture surgery.' Results: A total population of 3.4 million patient records was queried in the National COVID Cohort, identifying 2, 032 participants with ankle fracture surgery. The age range of the overall group was 18-98 years. Comparing COVID-19-positive to COVID-19-negative, the age (48.9 years vs 47.7 years) and gender (66.7% female vs 55.1% female) distribution of each group were comparable (both p>0.05). COVID-19-positive comprised 2.4% of the group (n=48). The length of stay was 4.7 days longer in the COVID-19-positive group (8.7 days vs 4.0 days, p<0.001). Higher proportions of COVID-19-positive patients who required invasive ventilation (12.5% vs 3.2%, p<0.002). The number of outcomes for mortality was too few to report. Conclusion: Based on the initial results, rotational ankle fractures requiring surgery necessitated longer hospitalizations in COVID-19-positive patients during the COVID-19 pandemic than in patients without the virus. The average increased length in hospitalization was, on average, about 6 days. When treated in isolation, ankle fractures can often be treated on an outpatient basis, and a multiple-day increase in average hospital stay is substantial. Though the overall complication profiles (with the exception of pulmonary disease) were similar, lengthy hospital stays could lead to delays in the recovery and rehabilitative process, and functional outcomes could not be determined in our study.